An exploratory spatiotemporal analysis of domestic disturbance calls for service in 2020: The case of Tampa, Florida, USA - Lersch, Kim M. (International journal of comparative and applied criminal justice, 2024)
As the world continues to struggle with the effects of the COVID-19 pandemic, there has been much speculation on the impact of the virus on crime rates, especially domestic violence. Researchers have largely adopted a routine activities explanation for increased levels of domestic violence, where disruptions in patterns of daily life caused by lockdowns increased the opportunity for such events to occur. The purpose of this manuscript was to utilise emerging hot spot analysis to explore spatiotemporal changes in the number of calls for service for domestic disturbance from 1 March 2020 – 31 December 2020 in the City of Tampa, FL USA based on critical time frames for restrictions and recovery. As predicted by opportunity theory, there was a statistically significant decline in the counts of calls over the 10-month period. Additionally, sporadic hot spots were found at some locations during times of heightened restrictions. Locations with sporadic hot spots coincided with census tracts reporting lower education levels; higher levels of poverty, unemployment, single parent households; and more minority residents.